Chinese Journal of Integrative Medicine - Chen, Keji.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Chinese Journal of Integrative Medicine seeks to promote international communication and exchange on integrative medicine as well as complementary and alternative medicine (CAM) and provide a rapid forum for the dissemination of scientific articles focusing on the latest developments and trends as well as experiences and achievements on integrative medicine or CAM in clinical practice, scientific research, education and healthcare.
Keywords: Medicine; Medicine/Public Health, general